1989
DOI: 10.1021/om00105a018
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical rearrangements of stable silenes

Abstract: deep purple (the color of Fp2). We could not detect any other organic products.Preparation of Enolate Complexes 6c,d and 8c,d. 1,3-Dioxolanes (acetals) of -halo ketones were prepared by the published method.32 NaFp or Na/KFp* (10 mmol) in THF (10 mL) was added to a THF solution (20 mL) of appropriate 1,3dioxolane (12 mmol) at -78 °C. After the mixture was stirred for 3 h at room temperature, the volatiles were removed under reduced pressure. The product was extracted with ether (100 mL) and filtered through si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 0 publications
1
37
0
Order By: Relevance
“…The 29 Si NMR chemical shift for the 1,1-disilylsubstituted silenes 5a-5e vary in the range of 41-54 ppm (Table 1) [83,84], which is comparable to the 29 Si chemical shift of the parent silene (53.8 ppm according to high-level ab initio calculations [15]). This suggests that the Me 3 Si group resembles hydrogen when it comes to its effect on 29 Si NMR chemical shifts of silenes.…”
Section: Nmr Chemical Shiftsmentioning
confidence: 72%
“…The 29 Si NMR chemical shift for the 1,1-disilylsubstituted silenes 5a-5e vary in the range of 41-54 ppm (Table 1) [83,84], which is comparable to the 29 Si chemical shift of the parent silene (53.8 ppm according to high-level ab initio calculations [15]). This suggests that the Me 3 Si group resembles hydrogen when it comes to its effect on 29 Si NMR chemical shifts of silenes.…”
Section: Nmr Chemical Shiftsmentioning
confidence: 72%
“…For example, reaction of LiMe with 7 and 10, respectively, generates after 2-3 days the highly air-and moisture-sensitive branched lithium silanides Li-18 [70,71] and Li-19 [72] ( Figure 4). Similarly, branched polysilane 21 [73] can be converted into Li-22 [74] in good yields ( Figure 5).…”
Section: Cores Spacers and Wingsmentioning
confidence: 99%
“…The tris(trimethylsilyl)silyl ('sisyl') lithium reagent is prepared by deprotonation of tris(trimethylsilyl)silane using an alkyl lithium reagent. The related alkyl bis(trimethylsilyl)silyl lithium species have been prepared by several methods (Scheme 7) 26 . The silyl lithium reagents, which are yellow to orange to brown in colour, can be remarkably stable; for example, phenyl bis(trimethylsilyl)silyl lithium forms a recrystallizable pale yellow solid 'ate' complex with THF with the stoichiometry Ph(Me 3 Si) 2 SiLiÐ3THF.…”
Section: Silyl Metallic Speciesmentioning
confidence: 99%
“…The acyl silane unit is thus acting as a formal geminal diradical species. An interesting development of this reaction includes a stannyl group at the halo-(or xanthate-) bearing carbon atom, cyclization of an˛-stannyl radical then resulting in formation of an˛-stannylated silyloxy radical, from which the stannyl unit is lost, providing a regiospecific synthesis of cyclic silyl enol ethers (Scheme 86) 200 Cycloaddition reactions of acyl silanes appear to be rare, but Brook has shown that˛-silyloxy bis(trimethylsilyl)silenes (52), generated photochemically from acyl tris(trimethylsilyl)silanes (vide infra, Section IV.A.4), undergo [2 C 2] and [4 C 2] cycloaddition reactions with ketones, and [4 C 2] cycloaddition reactions with less bulky acyl silanes, as illustrated in Scheme 87 17,24,26,72,73,201 …”
Section: Cyclization Reactionsmentioning
confidence: 99%
See 1 more Smart Citation